(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
This paper examines the visual and narrative discourse as a representation built through articles and photographs published in National Geographic on the island of Jamaica. It highlights the strategies and the various tropes, stereotypes, and repetition that helped create an image of the island territory and its population over several decades of the twentieth century.